An essay on the nature & significance of economic science - Robbins,Lionel (London : Macmillan, 1972)
The essay is the subject matter of economic science and the nature of generalisations of which economic science consists
Includes index
Includes bibliographical footnotes
obn23/01/2019
Loans
Keywords: Economics